Model Pembelajaran Problem Based Learning dalam Meningkatkan Kemampuan Memecahkan Masalah HAM pada Mata Pelajaran PKn Siswa Kelas Xi di SMKN 4 Kota Serang Tahun Pelajaran 2022/2023 - Herawati, R Teti (Aufklarung: Jurnal Pendidikan, Sosial dan Humaniora, 2022)
This classroom action research aims to improve the ability of class XI students of SMKN 4 Serang in addressing human rights issues in Civic Education subjects. This research uses the Action research method, starting from: a) planning, b) action and observation, c) reflection. The research process was carried out into two cycles. The research subjects were class XI students, with a total of 37 students, consisting of 3 boys and 34 girls. Tests, observations, interviews, and documentation studies were used to obtain data. The data analysis technique used was quantitative data analysis. After the application of the Problem Based Learning model, the results of the average value/score on student activities or behavior that are relevant to the learning process show an increase/increase from the first cycle to the second cycle of 15.22%. Then for student activities that were less relevant to learning in the first cycle, it decreased in the second cycle by 12.01%. Associated with students’ understanding of human rights issues in the first and second cycles experienced an increase, with an average score of 0.89%. An increase also occurred in learning completion between the first and second cycles of 15.14%